Pengaruh Pelaksanaan Work From Home (WFH) Terhadap Tingkat Kinerja Pegawai Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Polewali Mandar - Trisno Trisno; Saharuddin Saharuddin; Ihsan Ihsan (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This research aims to determine the effect of implementing work from home (WFH) on employee performance levels at the Polewali Mandar Regency Population and Civil Registration Service. The number of samples in this study was 60 people and the research method used data collection techniques using questionnaires. The results of data analysis based on a simple regression test and partial hypothesis testing (t test) show that the calculated t has a value of 7,642 which is > than the t table (2,001). Work From Home has a positive influence on the performance of employees at the Polewali Mandar Regency Population and Civil Registration Office. Conclusion: So, Ha is accepted and H0 is rejected.